Traditional Birth Attendants (TBAs) Positioning on Strengthening Partnership with Midwives (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Background of this research was the still high number of infant mortality and high use of Traditional Birth Attendants (TBAs). The This study aims aimed to determine TBAs positioning on the effort of strengthening partnership with midwives. A number of pregnant women, TBAs, and midwives become became informants, through in-depth interviews and focus group discussions. The results showed positioning TBAs still needed with different roles but side by side with midwife role, used by primi and multi pregnant women before and during pregnancy, during and after birth. The requirement forrequirement for TBAs was derived from parents as a cultural heritage, whereas the requirement for midwife obtained was from formal and non- formal information. The TBAs services toward maintain family health care including include cultural events. The midwife is givingserved professional servicescare. The partnership includes clients registration, motivation, abnormalities early detection. There has had been an unwritten financing unwritten agreement. The TBAs midwife partnership needs to be strengthened through legislation and , communication to diverse audiences in order to form the right positioning.